1969
DOI: 10.1159/000179741
|View full text |Cite
|
Sign up to set email alerts
|

A Study by Continuous Microperfusion of Water and Electrolyte Movements in the Loop of Henle and Distal Tubule of the Rat

Abstract: In the intact rat, short loops of Henle, distal and proximal tubules were studied by microperfusion. The same loop of Henle was perfused at 4 or more perfusion rates and net and fractional absorption of sodium was determined. When the perfusion rate increased a greater net amount of sodium was absorbed but the fractional absorption of sodium decreased from 80% at 10 nl/min to 50% at 40 nl/min. The fractional absorption of water fell from 65% to 30% with the same change in perfusion rates. In the distal tubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(56 citation statements)
references
References 7 publications
6
50
0
Order By: Relevance
“…Similarly, at the early distal micropuncture site, measurements of absolute total C02, chloride, and volume reabsorption were increased after ANF administration. Again, the slight decline in fractional solute and volume reabsorptive rates (e.g., the decrease in fractional chloride reabsorption from 0.96±0.01 to 0.91±0.01, P < 0.005) was consistent with the normal response to increased flow by loop transport processes (23,24).…”
Section: Resultssupporting
confidence: 64%
“…Similarly, at the early distal micropuncture site, measurements of absolute total C02, chloride, and volume reabsorption were increased after ANF administration. Again, the slight decline in fractional solute and volume reabsorptive rates (e.g., the decrease in fractional chloride reabsorption from 0.96±0.01 to 0.91±0.01, P < 0.005) was consistent with the normal response to increased flow by loop transport processes (23,24).…”
Section: Resultssupporting
confidence: 64%
“…Borenstein et al (1983) reported that injection of atrial extract into anesthetized rats increased total and medullary blood flow in the kidney. In the present study, the prolonged kaliuresis was accompanied by the diuresis, which suggests that urine flow into the distal tubule may have increased after the injection of a-hANP, since it has been shown that potassium secretion is increased when flow into the distal tubule is increased (Malnic et al 1966;Morgan and Berliner 1969;Kunau et al 1974; Khuri et al 1975;Reineck et al 1975;Diezi et al 1976). This increase in urine flow into the distal tubule could have been elicited by the dissipation of corticomedullary osmotic gradient by medullary washout.…”
Section: Resultssupporting
confidence: 58%
“…However, when tubules were perfused with solution 3, volume absorption was inhibited by (19). Effect of metabolic alkalosis.…”
Section: Resultsmentioning
confidence: 99%